1986
DOI: 10.1891/0886-6708.1.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Victims of Serious Violence and Their Criminal Behavior: Subcultural Theory and Beyond

Abstract: This paper looks at the relationship between the experiences of the victim of a serious crime and that of the offender. It shows that, in some cases, the victim experience is an important predictor of criminal behavior. An analysis of self-reported and officially recorded offense and victimization data supports the hypothesized relationship between victim and offender experiences. The results have implications for subcultural theory and a dynamic analysis of how patterns of assaultive violence are created and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 0 publications
1
53
0
Order By: Relevance
“…Research in these areas has the potential to shed new light on the causes of selfcontrol, the causes and consequences of victimization, and the manner in which strain impacts crime. More generally, this research may help us better link those literatures dealing with victimization and the causes of crime; an important task given the extensive overlap between offenders and victims (e.g., Lauritsen, Sampson, & Laub, 1991;Jensen & Brownfield, 1986;Regoeczi, 2000;Singer, 1986). Notes 1.…”
Section: Discussionmentioning
confidence: 99%
“…Research in these areas has the potential to shed new light on the causes of selfcontrol, the causes and consequences of victimization, and the manner in which strain impacts crime. More generally, this research may help us better link those literatures dealing with victimization and the causes of crime; an important task given the extensive overlap between offenders and victims (e.g., Lauritsen, Sampson, & Laub, 1991;Jensen & Brownfield, 1986;Regoeczi, 2000;Singer, 1986). Notes 1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals who engage in crime may put themselves at risk for retaliation from former victims (Jacobs and Wright 2006;Singer 1986;Stewart et al 2006), and may be more likely to come into contact with violent persons while they commit offenses or use drugs and alcohol during high-risk times (e.g., after dark) and in high-risk settings (e.g., in the absence of capable guardianship). It is therefore not surprising that prior work has found various forms of crime and delinquency to be some of the strongest correlates of victimization, independent of factors such as gang membership, peer associations, leisure activities, and demographic characteristics (e.g., age, sex, and race) (Haynie and Piquero 2006;Pauwels and Svensson 2011;Peterson et al 2004;.…”
Section: Structural Disadvantage and The Context Of Victimizationmentioning
confidence: 99%
“…For example, although their approaches were not rooted in GST, Singer (1986), Fagan, Piper, and Cheng (1987), and Zhang, Welte, and Wieczorek (2001) each found significant effects of victimization on delinquency. The latter study used panel data and observed that while delinquency did increase later victimization, there also were apparent short-term effects of victimization on delinquency.…”
Section: Victimization As a Form Of Strainmentioning
confidence: 99%